2021
DOI: 10.1111/area.12709
|View full text |Cite
|
Sign up to set email alerts
|

The city‐island‐state, wounding cascade, and multi‐level vulnerability explored through the lens of Malta

Abstract: The city-island-state, wounding cascade and multi-level vulnerability explored through the lens of Malta.Accepted for publication in Area. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…The event is confirmed by (a) reliable source(s), but an element of the event remains questionable or unknown 549 2 Probable event Recognised as an event within the catalogue, but more data are required to confirm occurrence and impact 212 1 Questionable event Based on inference, modelling or physical data only. This may be questionable than they were in the past (Schembri 2003;Vella et al 2005;Ciarlò 2017;Main et al 2021). Third, it is highly probable given the nature of the evidence discussed in Sect.…”
Section: Confirmed Eventmentioning
confidence: 92%
See 1 more Smart Citation
“…The event is confirmed by (a) reliable source(s), but an element of the event remains questionable or unknown 549 2 Probable event Recognised as an event within the catalogue, but more data are required to confirm occurrence and impact 212 1 Questionable event Based on inference, modelling or physical data only. This may be questionable than they were in the past (Schembri 2003;Vella et al 2005;Ciarlò 2017;Main et al 2021). Third, it is highly probable given the nature of the evidence discussed in Sect.…”
Section: Confirmed Eventmentioning
confidence: 92%
“…Islands have been long-represented as having high levels of exposure to environmental extremes owing to the complex interplay of a variety of factors (Pelling and Uitto 2001; Méheux et al 2007;Wisner and Gaillard 2009). Recent research has found that this is particularly apparent for advanced, independent and heavily urbanised island states, such as the city-island-state 1 of Malta (Main et al 2021). There is some research which has considered the hazardous history of economically more advanced islands and archipelagos where hazards occur frequently and/or where there are frequent reminders of the hazardousness of the place.…”
Section: Introductionmentioning
confidence: 99%
“…The city-island-state of Malta, also known as the Maltese Islands, is a small, European Union (EU), archipelagic island state comprising three principal islands: Malta (246 km 2 ); Gozo (67 km 2 ) and Comino (2.7 km 2 ) (Schembri 2019;Main et al 2021). Located in the central Mediterranean (Fig.…”
Section: Maltamentioning
confidence: 99%
“…First, it is "only because of the probabilistic nature of extreme events impacting vulnerable people that [the island state] has not been more severely affected in recent years" (Main et al 2018, p. 131). Secondly, rapid and ongoing expansion of the urban footprint, including significant coastal development with over 35 % of Malta's littoral classified as urban in 2017 (up from 5 % in 1990), is making areas and their increasing population more exposed and vulnerable than they were in the past (Schembri 2003;Vella et al 2005;Ciarlò 2017;Main et al 2021). Thirdly, it is highly probable given the nature of the evidence discussed in Sect.…”
Section: The Cataloguementioning
confidence: 99%
See 1 more Smart Citation